Pendampingan Guru Dalam Menerapkan Strategi Pengenalan Membaca Phonics Method - Ngura, Elisabeth; Fono, Yasinta Maria; Efrasia Odo, Maria (PELITA NUSA TENGGARA, 2025)
The purpose of this community service activity is to explain how to introduce vocabulary reading strategies through the phonics method to teachers at Kober Peupado Malanuza and to explain the output products generated through the phonics strategy in this community service activity. The phonics method is one of the reading methods, where